Loss of endothelial furin leads to cardiac malformation and early postnatal death. - Kim, W; Essalmani, R; Szumska, D; Creemers, J; Roebroek, A; D'Orleans-Juste, P; Bhattacharya, S; Seidah, N; Prat, A (2012)
In mammals, seven proprotein convertases (PCs) cleave secretory proteins after basic residues, and four of them are called furin-like PCs: furin, PC5, PACE4, and PC7. In vitro, they share many substrates. However, furin is essential during development since deficient embryos die at embryonic day 11 and exhibit multiple developmental defects, particularly defects related to the function of endothelial cells. To define the role of furin in endothelial cells, an endothelial cell-specific knockout (ecKO) of the Furin gene was generated. Newborns die shortly after birth, indicating that furin is essential in these cells. Magnetic resonance imaging revealed that ecKO embryos exhibit ventricular septal defects (VSD) and/or valve malformations. In addition, primary cultures of wild-type and ecKO lung endothelial cells revealed that ecKO cells are unable to grow. Growth was efficiently rescued by extracellular soluble furin. Analysis of the processing of precursors of endothelin-1 (ET-1), adrenomedullin (Adm), transforming growth factor β1 (TGF-β1), and bone morphogenetic protein 4 (BMP4) confirmed that ET-1, Adm, and TGF-β1 are in vivo substrates of endothelial furin. Mature ET-1 and BMP4 forms were reduced by ~90% in ecKO purified endothelial cells from lungs.